The Impact of Knowledge Management Success Factors on Electronic Business in Jordanian Telecom Companies - Diala Kh. Al Daradkeh; Mohammed A. Abu Rumman; Samer M. Arqawi; Mazen J. Al Shobaki; Samy S. Abu-Naser (International Journal of Supply Chain Management, 2020)
Abstract: The study aimed to identify the impact of knowledge management success factors represented (organizational culture, administrative leadership, organizational structure, information technology infrastructure, standards) on electronic business (electronic information, electronic communications, electronic work flow), and the study community included all employees in Jordanian telecom companies, where the three telecommunications companies (Umniah, Zain, Orange) agreed to participate in the study, and (240) questionnaires were distributed to employees in those companies, and (191) questionnaires were retrieved, of which (188) were valid questionnaires for analysis with an actual response amount of (78.3%), which is similar to the final study sample. The study used the descriptive analytical method, and assumed a positive impact of the factors of success of knowledge management on electronic business in Jordanian telecom companies. The results showed that there is an awareness of the factors of success of knowledge management among employees in Jordanian telecom companies, where the arithmetic averages for the organizational culture variables, information technology infrastructure and knowledge measures came within the level of high importance, and the variable of administrative leadership and the organizational structure variable came within the level of intermediate importance in the current study, as well all averages of e-business dimensions came within the high level of importance, as well as the overall e-business variable, in addition to that, the results indicated a positive impact of the factors of success of knowledge management on e-business in Jordanian telecom companies; as the variable of knowledge management success factors explained (65.7%) of the variance in e-business, and the results also indicated that the variable of information technology infrastructure was the most influencing electronic information, and the second ranked in the impact of organizational culture, while the variables of administrative leadership do not affect the organizational structure and measures of knowledge on electronic information, and the results also showed that the variable of the information technology infrastructure ranked first in the impact on electronic communications, followed by the effect of the variable of organizational culture, and then the organizational structure variable, while the administrative leadership and knowledge standards variables do not affect, finally it showed the results indicated that the variable of the IT infrastructure was the most influential in the electronic work flow, and came second in the organizational structure, and the organizational culture ranked third, and the fourth came the variable of administrative leadership, while the electronic work flow variable was not affected by knowledge measures. Based on the results, the study recommended the need to pay attention to the employees awareness of the importance of success factors Knowledge Management, given its impact on e-business, by maintaining the level of organizational culture, and constantly enhancing it, raising the level of awareness of managers and decision makers about the importance of knowledge management success factors and their impact on e-business, developing the capabilities of employees, and creating a special administrative unit, concerned with knowledge management and organization Its operations, in addition to adopting successful organizational structures that increase the level of knowledge, as well as the need to develop and promote electronic business in Jordanian telecom companies, by paying attention to the communication infrastructure, and providing modern electronic workflow systems, the study also recommended researchers to conduct other studies on management success factors Knowledge and e-business in other study societies and other organizational outputs.